From the valid Constitution to the living Constitution - Aróstica Maldonado, Iván (Derecho Público Iberoamericano, 2020)
This article identifies the different political-legal trends that threaten the foundations of constitutional stability and the rule of law, although not explicitly. The author claims that compromising constitutional stability and the rule of law is their logical consequence by producing tensions within the modern state.